Hydrothermally Synthesized ZnSnO3 Nanoflakes Based Low-Cost Sensing Device for High Performance CO2 Monitoring. (1st March 2023) - Singh, Ajeet; Yadav, Sanjay Kumar; Verma, Arpit; Sikarwar, Samiksha; Yadav, Bal Chandra
Abstract : This work reports a room temperature operative ZnSnO3 nanoflakes-based CO2 gas sensor. The perovskite ZnSnO3 nanoflakes are synthesized by a one-pot hydrothermal technique. The prepared material was characterized via XRD, SEM, UV-visible spectroscopy, and DLS measurement for confirming the crystal structure, surface morphology, optical properties, and size distribution. The X-ray diffraction pattern revealed that ZnSnO3 was in the orthorhombic phase and average crystallite size examined by the Scherrer formula was 8.05 nm. Optical studies were done by the UV–vis spectroscopy and a direct optical band gap was found to be 3.27 eV. The surface morphology of ZnSnO3 was found to nanoflakes are almost uniform dimensions. The fabricated sensor device of ZnSnO3 detected the CO2 gas at room temperature (RT) for different concentrations. The best sensor response was found to be 4.93 for 1000 ppm of CO2 whereas at 200 ppm the response and recovery times were found to be 5.92 s and 7.23 s respectively. HOMO-LUMO gap energy of ZnSnO3 without and with interaction from CO2 molecule was found 1.165 eV and 1.577 eV, respectively. DFT studies are used for a better understanding of sensing mechanisms.